Diseño de un sistema de gestión de calidad bajo la norma ISO 9001:2008 para la empresa de consultoría y capacitación Empower Consult del Ecuador S.A. de la ciudad de Quito - Paccha Jiménez, Rocío Maribel (2015)
This study aims to “Designing a Quality Management System under ISO 9001:2008 for Consulting and Training Empower Consult the Ecuador SA, of Quito.” The design of the Quality Management System has been divided into 2 steps, the first corresponding to the analysis of the current situation, where it was determined what requirements the company meets are empirically; tool was used in addition to the SWOT analysis in order to determine the Strengths, Weaknesses, Opportunities and Threats that the company currently has in the Ecuadorian market; conducting the second design Quality Management System, based on PDCA, where it is suggested and to the consideration of the company the following products: quality policy, scope of the QMS, process map and quality objectives . With respect to the QMS documentation, seven stages for development was determined and the procedures and instructions required by the Standard was developed such as: Procedure for control of documents and records, Instructions for preparing and coding documents, procedure for internal audits Procedure for nonconforming product and process for corrective and preventive actions; Needless to say, for each procedure was performed the respective registers. We have determined the cost of the design phase as well as the further training of employees in the areas of Process Management, Basics and requirements of ISO9001: 2008 and Internal Audits.